Effects of polyethylene glycol in self-curing mortar containing fly ash - Mohamad D.; Beddu S.; Sadon S.N.; Kamal N.L.M.; Itam Z.; Alshugaa Y.A.A. (Medwell Journals, 2023)
Curing is maintaining a sufficient water and temperature in concrete through its early periods to get the aimed properties of concrete. Curing is critical in production of concrete to ensure that concrete will have the durability and strength. In order to make the concrete cured by itself, a chemical called Polyethylene Glycol 400 (PEG) is used where it helps in water retention throughout the concrete during curing process. In this project, PEG and Fly Ash (FA) were added as a self-curing agents in mortar to determine the effects of self-curing agents in term of compressive strength. The mortar ratio was 1:2.75 (cement:sand). PEG was added first with different percentage 1, 2 and 3% by weight of cement. Then, FA was added with different percentage 20, 40, 60, 80 and 100% by weight of cement. The w/c ratio was 0.45 to ensure the workability. All mortars were exposed to the fresh air (in the laboratory environment with 25C for curing to see the effect of self-curing agents. The result showed that, self-curing agents have improved the strength of mortar. The mortar using PEG has scientifically increased the strength by 31% compared to conventional mortar. And 1% was the optimum percentage. FA enhanced the early age strength by 80% compared to normal mortar. Also, 20% of FA was the optimum percentage. Medwell Journals, 2017.